Physician's Knowledge and Practices Surrounding Low-Dose Aspirin for Preeclampsia Risk Reduction - Martinez-King, L Carolina; Machiorlatti, Michael; Ogburn, Tony; Salcedo, Jennifer (American Journal of Perinatology, 2023)
Objective Preeclampsia is a leading cause of pregnancy-related deaths. Up to 60% of maternal deaths associated with preeclampsia may be prevented. Clinical trials have shown that low-dose aspirin reduces preeclampsia up to 30% among women at increased risk. Since 2014, multiple professional societies and the U.S. Preventive Services Task Force have released guidelines on the use of low-dose aspirin to reduce the risk of preeclampsia. We aimed to evaluate physician's knowledge and practices surrounding low-dose aspirin for preeclampsia risk reduction.Study Design We distributed an anonymous electronic survey to licensed physicians in the Rio Grande Valley of Texas who provide prenatal care, including general obstetrician–gynecologists, maternal fetal medicine subspecialists, and family medicine physicians. The survey consisted of 20 items assessing demographics, provider practices, and knowledge on the use of low-dose aspirin for preeclampsia risk reduction.Results We received 48 surveys with a response rate of 55%. More than 90% of physicians reported recommending low-dose aspirin for preeclampsia risk reduction, of which 98% correctly identified the dose. Of the physicians recommending aspirin, 83% initiate dosing between 12 and 16 weeks, but only 52% continue it until the day of delivery. Nearly 80% of respondents identified that one high-risk factor for preeclampsia is an indication for prophylaxis, but only 56% identified that two or more moderate risk factors should prompt aspirin recommendation.Conclusion Despite clear professional guidelines, physicians demonstrated gaps in knowledge and differences in practices. Enhancing screening tools to assess patient's risk of developing preeclampsia and tailored medical education on moderate risk factors are needed to identify patients who may benefit from this intervention. Increasing the use of aspirin in patients at risk is critical given the benefits of low-dose aspirin in the reduction of poor maternal and neonatal outcomes related to preeclampsia.Key Points
Keywords: preeclampsia; aspirin; provider's knowledge; prevention; maternal mortality; prophylaxis